Dampak Konflik dan Stress Kerja terhadap Kinerja pada PTPN IV Dolok Sinumbah - Resna Napitu; Wico Jontarudi Tarigan (Universitas Batanghari, 2022)
This study aims to determine the impact of conflict and work stress on employee performance at PTPN IV Dolok Sinumbah. Where the independent variabels are conflict and Job Stress. Meanwhile, the dependent variable is Employee Performance. This study uses survey research methods and data collection techniques used are observation, interviews and documentation. The population used in this study were all employees of PTPN IV Dolok Sinumbah, totaling 74 people, while the sample in this study were employees at PTPN IV Dolok Sinumbah, amounting to 19 people with a simple random sampling technique in getting sources who wanted to be interviewed. The results of this study indicate that conflict has an impact on employee performance at PTPN IV Dolok Sinumbah. Work stress has an impact on employee performance at PTPN IV Dolok Sinumbah. Conflict and work stress together have an impact on emloyee performance at PTPN IV Dolok Sinumbah.companies can minimize conflict and work stress by providing conflict management and stress management training in each well- managed sub-unit sp that it has a positive impact on employees, esepecially employees with the haviest work preasure.